RASPBERRY PI SEBAGAI PEMANTAU RUANG LABORATORIUM MENGGUNAKAN METODE PEREKAMAN TERJADWAL BERBASIS DATABASE - Usman Zulhijah Muhammad; Eko Pamuji (Politeknik Negeri Malang, 2020)
Practicum activities in higher education especially in State Polytechnic of Malang are generally carried out in a laboratory and based on a predetermined schedule. In the practicum activities are usually used equipment and practical materials borrowed by students from cabinets or warehouses for storage of tools and materials. In addition, in the laboratory where the practicum is carried out there are equipment and personal belongings belonging to students or teachers. From the experience that has happened, some campus-owned lab equipment and materials have been damaged and lost, or the personal property of students or teachers who have been left behind and even lost. Monitoring and recording using ordinary cameras has a disadvantage, that is, we cannot adjust the recording schedule that changes every day based on the space usage schedule. And record data is still one part or not grouped based on space usage schedule. Therefore, it is necessary to make a system that can monitor and record the process of laboratory practicum activities based on space usage schedule. In this study a system will be made using the embeded Raspberry Pi system and a camera module with MySQL as the database, this system is designed and created so that it can be used to record the laboratory practicum activities based on the space usage schedule in the database